Pemetaan Pengajian al-Qur’an di Perguruan Tinggi Agama Islam (PTAI): Kajian di Institut Ilmu al-Qur’an (IIQ) Jakarta-Indonesia: The Mapping of Quranic Studies in Islamic Higher Education (PTAI): A Study at Institute of Quran Studies (IIQ) Jakarta-Indonesia - Achmad, Nurjanah; Abdullah, Mustaffa; Mohamed Adnan, Mohamad Azrien (Journal of Islamic Educational Research, 2022)
The Quranic Studies in Indonesia has been rapidly evolving since Islam arrived in the archipelago. However, an extensive mapping of the Quranic Studies is difficult to find in order to sustain the development of the Quranic Studies in Islamic Higher Education (PTAI). This study therefore aims to map the study of the Quranic Studies that is the basis of other Islamic education. In order to enhance the scientific field in Quranic Studies during the modern era, it is necessary to link the curriculum and syllabus for the study of the Quran with the integration of different scientific disciplines. In addition, other discussions such as teaching methods, teaching media, reference materials and assessment methods cannot be ignored to be equivalent Quranic Studies with other areas of Islamic studies. By a descriptive qualitative approach, the results of this study have shown that mapping of the Quranic Studies in Department of al-Qur'an and Exegeses Science (IAT) of Institute of Quran Studies (IIQ) different characteristics from the other PTAIs. It was conducted systematically and effectively so that it became the originator of the famous IIQ as a Quranic campus icon in Indonesia.